2009
DOI: 10.1299/jmmp.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance of AISI316L Steel Modified by Pre-FPP Treated DLC Coating

Abstract: In order to improve the adhesion strength of the DLC coating, Fine Particle Peening (FPP) treatment was employed as pretreatment for DLC coatings. FPP treatment was performed using SiC shot particles, and then the AISI316L steel was DLC-coated. The FPP treatment increased the surface roughness of the specimen, and a Si-rich layer was formed on the surface because of the mechanical mixing of SiC shot particles into the steel substrate. Reciprocating sliding wear tests were conducted to measure the friction coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…In this case, both the particle and substrate are ductile so that microstructure is modified due to transferring and mixing phenomena. On the other hand, brittle particles do not form lamellar microstructure, but are embedded into substrate directly Nanbu et al, 2009). Similarly, little mixing should be induced in the brittle substrate because of lack of plasticity of material.…”
Section: Effect Of Particle and Substrate Characteristics On The Tranmentioning
confidence: 99%
“…In this case, both the particle and substrate are ductile so that microstructure is modified due to transferring and mixing phenomena. On the other hand, brittle particles do not form lamellar microstructure, but are embedded into substrate directly Nanbu et al, 2009). Similarly, little mixing should be induced in the brittle substrate because of lack of plasticity of material.…”
Section: Effect Of Particle and Substrate Characteristics On The Tranmentioning
confidence: 99%
“…This implies that the DLC film was deposited along the original surface. Figure 6 shows the friction coefficients of each specimen as a function of sliding cycles [12]. The Polished-D and FPP-D series with DLC coating show lower friction coefficients during the earlier stages of sliding compared to those of the Polished and FPP series without DLC coating.…”
Section: Methodsmentioning
confidence: 99%
“…The authors [10,11] reported that small chips of shot particles were embedded into the substrate surface during the FPP treatment. The surface layer created by the treatment was expected to enhance the DLC/substrate interfacial adhesion, resulting in good tribological performance.…”
Section: Introductionmentioning
confidence: 99%
“…性が改善されることを明らかとしている.さらに,この FPP は,被処理材の結晶粒を微細化させるのみならず, 被処理面に粒子移着層を形成 (16) (17) させることが可能である.また,この移着粒子は二段目の窒化挙動に影響を及 ぼす (18) EDX),X 線光電子分光装置(X-ray photoelectron spectroscopy: XPS)を用いて微視組織の観察および分析を行った.また, 被処理面の結晶構造分析には, X 線回折 (X-ray diffraction: XRD) 装置を用い, X線入射角度10°, X線源CuKα (波長0.154nm) , 電圧 40kV,電流 40mA,2θ = 20~90°の条件で行った.また,得られた回折プロファイルの半価幅をもとに,式(1)を用 いて被処理材の結晶子寸法 D(Å)を算出した (19) Nitriding time 1/2 , hour…”
Section: Plasma Nitriding Behavior Of Pure Iron Pre-treated With Fineunclassified